Cálculo de parâmetros de malhas de aterramento em geometrias não convencionais - Pires, Thyago Gumeratto (2016)
This work presents the methodology for the calculation of the ground resistance, the ground potential rise, the surface potential, the touch voltage and step voltage in grounding grids with any geometry and buried at any depth within strati ed soil in two layers. The values of potential, touch voltage and step voltage are obtained at any point over the grid. The proposed equation uses the images and the average potential methods. The main feature of this modeling in relation to the other methods is the possibility of calculation of grids containing electrodes positioned at any distance and at any angle. The results obtained with the proposed methodology are presented and discussed.